Upaya Peningkatan Manajemen Diri Penderita Hipertensi Melalui Senam Ce'Esi (Cegah Hipertensi) Di Wilayah Kerja Puskesmas Cijedil. Cugenang”: Upaya Peningkatan Manajemen Diri Penderita Hipertensi Melalui Senam Ce'Esi (Cegah Hipertensi) Di Wilayah Kerja Puskesmas Cijedil, Cugenang - Ayu, Shinta Arini; Dewi, Sri Kurnia; Utami, Nofya; Anggraeni, Rani; Nuryani, Siti (Ruang Ide Publisher, 2023)
Abstract Exercise to prevent hypertension that is carried out routinely will provide health benefits that will indirectly have the effect of increasing heart function and lowering blood pressure. As well as reducing the accumulation of fat on the walls of blood vessels in order to maintain their elasticity. The purpose of this community assessment is to examine the impact of Ce Esi gymnastics on reducing blood pressure in hypertensive patients. A total of 30 respondents with hypertension were selected from Cibeureum Village in the working area of ​​the Cijedil Health Center, Cugenang District. The method used was the experimental method (pre-experimental design) using a one-group pre-test-post-test design. Non-probabilistic sampling technique using purposive sampling. The results and administration of the intervention showed astolic and diastolic blood pressure. It is hoped that the Ce Esi gymnastics will be carried out routinely by hypertension sufferers in the Cijedil Kes Cugenang Health Center area, especially by residents of Ciebereum village and make it a routine routine. not less and once a week in a wider local area, as one of the efforts to manage hypertension.